Experience in the development of a system for repeated prosthetic heart valves - E. A. Ovcharenko; K. Yu. Klyshnikov; A. N. Stasev; A. V. Evtushenko; I. K. Khalivopulo; D. V. Borisenko; T. V. Glushkova; A. V. Ivanova; I. V. Dvadtsatov; S. S. Krutitsky; Yu. A. Kudryavtseva; O. L. Barbarash; et al. (Сибирский научный медицинский журнал, 2023)
The failure of heart valve bioprostheses, requiring repeated intervention to replace them, is a serious drawback that narrows the scope of such devices. The present study demonstrates the experimental investigation of a medical device designed to partially solve the problem of repeated interventions on heart valves, primarily with an emphasis on reducing the duration and trauma of such procedures due to the sutureless balloon implantation method of the «valvein- valve» method.Material and methods. The paper presents a series of in silico, in vitro and in vivo experiments to evaluate various aspects of the device under development. Numerical modeling of the final shape setting to the supporting frame of the heart valve prosthesis to select the most promising concept for prototyping was carried out in the Abaqus/CAE (Dassault Systèmes, France) based on the finite element method. The selected optimal support frame model was prototyped in the form of a series of prosthesis samples of four standard sizes for hydrodynamic studies of quantitative characteristics in vitro. The study was carried out in the Vivitro Labs unit (Vivitro Labs, Canada), imitating the physiological mode of the heart, the prostheses were examined for the mitral position. The developed prototypes of the device were supplemented with related products, an implant holder and a balloon catheter, after which the proposed method of sutureless fixation was validated in an in vitro implantation procedure on a bovine heart model and a series of in vivo (n = 3) chronic experiments on animals.Results. In the course of numerical simulation, it was shown that in Model No. 3 of the supporting frame of the prosthesis, the smallest stresses occur – with an amplitude of up to 490 MPa. For other concepts (Models No. 1 and No. 2), this indicator was significantly higher, 543 and 514 MPa, respectively. Prototypes obtained on the basis of the selected shape of the support frame demonstrated satisfactory hydrodynamic characteristics: effective hole area 190-261 mm2, regurgitation volume 6–9 ml/cycle, average transprosthetic gradient 4.4–6.4 mmHg, depending on size. The study of the technology of sutureless balloon implantation in an in vitro model of the heart and the subsequent chronic experiment on sheep confirmed the main idea of the system – the possibility of a significant reduction in the duration of repeated prosthetics. It has been shown that the time of suture implantation of the “classic” frame prosthesis of the mitral valve is 23–29 minutes, with a total access time of 41–52 minutes. When implanting the experimental device, the sutureless prosthesis itself took 4–6 minutes, access time 24–29 minutes. At the same time, one-month results of an echocardiographic study of the operation of the prosthesis demonstrated satisfactory hemodynamics.Conclusions. This work demonstrates a consistent series of tests of the system being developed for repeated heart valve replacement, which substantiates some design solutions, confirms the effectiveness and viability of the chosen approach to sutureless minimally invasive implantation.